Giant bladder diverticulum: A rare cause of bladder outlet obstruction in children - William Appeadu-Mensah; A. A. J. Hesse; Mensah B Yaw (Wolters Kluwer Medknow Publications, 2012)
Giant bladder diverticula are rare causes of bladder outlet obstruction in children and have rarely been reported. [1] In this paper, we present three children with giant bladder diverticula who presented with bladder outlet obstruction within a year. Micturating cystourethrogram is important for investigating bladder outlet obstruction in children and was used to confirm the diagnosis in all the patients. The relationship between the diverticula and ureters varied, with the ureters running either through the wall of the diverticulum and opening directly into the bladder, or opening into the diverticulum. In one patient, there was a recurrence, which was excised successfully. Excision is important to reduce the risk of recurrence.